A Broadband High-Efficiency Dipole Array Based on Frequency Selective Surface and Integrated Feeding Structure - Hong Tang (IEEE, 2021)
In this paper, an ultra-wideband tightly couple antenna array based on a low-loss phase-modulated frequency selective surface and a microstrip-based feeding structure is reported. The proposed antenna array, which employs tightly coupled bow-tie elements, features a very low profile (1.08 $λ _{high}$ ). Specifically, a microstrip-to-parallel strip transition serves as an impedance transformer and a wideband balun to enable the array element to be excited with a 50 $Ω $ unbalanced feeding scheme. Additionally, one shorting sheet is employed to expand the bandwidth by shifting the common-mode to a higher frequency band. The presented design achieves a bandwidth of 13.66:1 (0.52 GHz – 7.10 GHz) with VSWR < 2.49 and simulated radiation efficiency greater than 96% across the whole band. To validate the design concepts, an $8×8$ array prototype is fabricated and characterized experimentally. The measured results match well with the numerical analysis.